Genetic and Phenotypic Characterization of the Novel Metallo-β-Lactamase NDM-29 From Escherichia coli - Ying Zhu (Frontiers Media S.A., 2021)
Objectives: The New Delhi metallo-β-lactamase (NDM) can hydrolyze almost all clinically available β-lactam antibiotics and has widely spread all over the world. NDM-29, a novel carbapenemase, was discovered in an Escherichia coli (19NC225) isolated from a patient with biliary tract infection in 2019 in China.Methods: Conjugation, transformation, cloning test, fitness cost, PacBio Sequel, and Illumina sequencing were performed to analyze the genetic and phenotypic characterization of blaNDM–29.Results: The susceptibility testing results showed 19NC225 was resistant to cephalosporins, carbapenems, combinations of β-lactam and β-lactamase inhibitors, and levofloxacin. Conjugation and transformation were performed to verify the transferability of NDM-29-encoding plasmid, and cloning test was conducted to prove the function of blaNDM–29 to increase carbapenem resistance. Furthermore, fitness cost test confirmed that the presence of NDM-29 exerts no survival pressure on bacteria. PacBio Sequel and Illumina sequencing were performed to analyze the genetic characterization of 19NC225, which contains two plasmids (pNC225-TEM1B and pNC225-NDM-29). pNC225-NDM-29, exhibiting 99.96% identity and 100% coverage with pNDM-BTR (an IncN1 plasmid from an E. coli in urine specimen from Beijing in 2013), showed responsibility for the multidrug-resistant (MDR) phenotype. Compared with blaNDM–1, blaNDM–29, located on pNC225-NDM-29, carries a G388A (D130N) mutation. The region harboring blaNDM–29 is located in an ISKpn19-based transposon, and two Tn6292 remnants are symmetrically located upstream and downstream of the transposon. The sequence results also indicated several important virulence genes.Conclusion: The findings of the novel carbapenemase NDM-29 could pose a threat to the control of antimicrobial resistance and arouse attention about the mutation of bacteria.